The Responsibilities of Housing Developers Due to Default in the Sale and Purchase Agreement of Home Ownership - Mudasir, Ahmad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to find out and analyze the implementation of the role of a Notary related to PPJB according to the applicable laws and regulations. to find out and analyze the responsibilities of housing developers due to defaults in the sale and purchase agreement of home ownership to consumers of Tlogomulyo residence Semarang, and to find out and analyze legal protection for consumers for the sale and purchase agreement that has been mutually agreed upon with the Housing Developer Tlgomulyo residence Semarang. Sociological juridical law research methods. The specification of this research uses descriptive analysis. The type of data used in this study is primary data which includes the 1945 Constitution; Act No. 1 of 2011; Basic Agrarian Law; the Consumer Protection Act, the Civil Code; The Criminal Code, as well as secondary data containing books and other supporting documents. Collecting research data using interview techniques and study of documents or library materials. The data analysis method used in analyzing the data is an interactive qualitative analysis model as proposed by Bodgan and Biklen. The research results show that the developer's responsibility is not only limited to what is stated in the agreement, but more than that, the developer must also be responsible for hidden defects/damage to the Tlogomulyo Residence Housing. Mutual protection for consumers for the PPJB which has been mutually agreed upon with the Tlogomulyo Residence Housing Developer, Pedurungan District, Semarang City, namely before PPJB can be carried out through deliberation to reach a consensus.Keywords: Agreement; Developer; Liability.